Plectin reinforces vascular integrity by mediating crosstalk between the vimentin and the actin networks - Osmanagic-Myers, Selma (J Cell Sci, 2015)
Mutations in the cytoskeletal linker protein plectin result in multisystemic diseases affecting skin and muscle with indications of additional vascular system involvement. To study the mechanisms underlying vascular disorders, we established plectin-deficient endothelial cell and mouse models. We show that apart from perturbing the vimentin cytoskeleton of endothelial cells, plectin deficiency leads to severe distortions of adherens junctions (AJs), as well as tight junctions, accompanied by an upregulation of actin stress fibres and increased cellular contractility. Plectin-deficient endothelial cell layers were more leaky and showed reduced mechanical resilience in fluid-shear stress and mechanical stretch experiments. We suggest that the distorted AJs and upregulated actin stress fibres in plectin-deficient cells are rooted in perturbations of the vimentin cytoskeleton, as similar phenotypes could be mimicked in wild-type cells by disruption of vimentin filaments. In vivo studies in endothelium-restricted conditional plectin-knockout mice revealed significant distortions of AJs in stress-prone aortic arch regions and increased pulmonary vascular leakage. Our study opens a new perspective on cytoskeleton-controlled vascular permeability, where a plectin-organized vimentin scaffold keeps actomyosin contractility ‘in-check’ and maintains AJ homeostasis.